2008
DOI: 10.1186/ar2389
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic compression counteracts IL-1β induced inducible nitric oxide synthase and cyclo-oxygenase-2 expression in chondrocyte/agarose constructs

Abstract: BackgroundNitric oxide and prostaglandin E2 (PGE2play pivotal roles in both the pathogenesis of osteoarthritis and catabolic processes in articular cartilage. These mediators are influenced by both IL-1β and mechanical loading, and involve alterations in the inducible nitric oxide synthase (iNOS) and cyclo-oxygenase (COX)-2 enzymes. To identify the specific interactions that are activated by both types of stimuli, we examined the effects of dynamic compression on levels of expression of iNOS and COX-2 and invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 59 publications
3
66
0
1
Order By: Relevance
“…Moderate levels of dynamic compression appear to inhibit some of the catabolic effects of interleukin-1 on articular chondrocytes [24,25]. However, proteoglycan (PG) loss in cartilage explants subjected to injurious compression and cultured in the presence of TNF-a was greater than that produced by either injurious compression or TNF-a treatment alone [26].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Moderate levels of dynamic compression appear to inhibit some of the catabolic effects of interleukin-1 on articular chondrocytes [24,25]. However, proteoglycan (PG) loss in cartilage explants subjected to injurious compression and cultured in the presence of TNF-a was greater than that produced by either injurious compression or TNF-a treatment alone [26].…”
Section: Introductionmentioning
confidence: 93%
“…Importantly, the two-week time course of the study by Ferretti et al [32] was much longer than the time course of this study. Further, low levels of in vitro dynamic compression seem to inhibit the catabolic effects of cytokines on articular chondrocytes [24,25,33], but a loading threshold may exist above which the protective effects of mechanical load are not observed [33]. Consistent with the findings of Li et al [33], dynamic unconfined compression was observed to upregulate CII and aggrecan expression relative to unloaded samples treated with TNF-a and TNF-a treatment was observed to upregulate ADAM-TS expression even in the presence of dynamic compression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The compression also prevented downregulation of ACAN in the presence of inflammation. 3,6 Similarly, compressive forces inhibited IL-1β-inducible nitric oxide synthase (INOS/NOS2A) and cyclooxygenase 2 (COX2)/prostaglandin G/H synthase 2 (PTGS2) expression 17,18 and upregulated PG synthesis and cell division in the presence or absence of IL-1β (Fig. 2).…”
Section: A Compressive Forces Regulate Cartilage Damage and Repairmentioning
confidence: 99%